Comparison of gingival health between mothers with preterm and term labor at Mahdieh Hospital between 2001 and 2002 - Zadeh Modarres Sh; Amooian B.; Bayat Movahed S.; Mohammadi M.; Sheikholeslam L.; Sheikholeslam F. (Tehran University of Medical Sciences, 2007)
Background and Aim: Low birth weight is a significant public health issue. Recent studies have suggested periodontal diseases as risk factor for preterm labor. The aim of this study was to assess the relation between gingival health and preterm labor in a sample of Iranian female population. "nMaterials and Methods: In this cross sectional study, 201 pregnant women without any systemic diseases or other risk factors like psychotic conditions were selected. Ninety-nine of them had term labor (infant≥37 weeks) and 102 had preterm labor (infant<37 weeks). Bleeding index, pocket depth and debris index were measured. Data were analyzed by Chi-square and Mann-Whitney tests with p<0.05 as the level of significance."nResults: Bleeding index, probing depth and debris index showed statistically significant differences between preterm and term labor mothers (P<0.001)."nConclusion: According to the findings of this study, there is a significant relationship between gingival health and duration of pregnancy. Consequently, periodontal diseases could be risk factor for preterm labor. Oral hygiene is strongly recommended to be included in pregnancy health programs.